Fuzzy Models of Information Security of the University Educational Process in the Conditions of Digitalization - Alexei DOLZHENKO; Irina SHPOLIANSKAYA; Leonid POTAPOV; Tatyana SHKODINA (Communications of International Proceedings, 2021)
In conditions of digitalization of the university educational process and enhancing the role of the distance learning in the context of pandemics, the Internet has become the major infrastructure that provides the platform for innovation. That creates a virtual space where universities and consumers of educational services actively interact. The development of modern approaches to University learning process management, based on the widespread use of telecommunications technologies, artificial intelligence, and big data analysis, leads to new distance learning practices. In the context of digital transformation, the idea and essence of information security of the University educational processes are changing due to the new threats and risks for universities and consumers of educational services. The significant uncertainty of the environment determines the risk factors of information security of the University's educational process. That makes it necessary to construct fuzzy models for assessing threats and risks of information security of the University's educational process. This paper presents a new approach for the risk assessment of the learning process information security based on the fuzzy inference system. A fuzzy network with Mamdani fuzzy inference allows you to perform the analysis of the parameters of information security risks. A fuzzy rule base was defined, and then it was evaluated by the Mamdani algorithm.
Keywords: Educational process; information security; risk; fuzzy model